Crop diversification and poverty reduction: The role of access to road in Niger - Tankari, Mahamadou Roufahi; Glatzel, Katrin; Demmler, Kathrin M. (African Association of Agricultural Economists, 2019)
Crop diversification is considered as a climate-smart agriculture practice widely adopted by smallholder farmers in Niger due to its many benefits including increased resilience, control of pests and diseases, yield stability, food diversity and poverty reduction. However, its impact on welfare may be limited when farm households do not have access to basic infrastructure such as roads, which are so crucial for access to markets. This paper aims to show how crop diversification affects farm households’ poverty status and severity under access to road constraints in Niger. The estimations are based on probit and tobit models using a panel data set provided by the Surveys of Living Conditions of Households and Agriculture of Niger for the years 2011 and 2014. To establish causal relationship, the identification strategy dealt with unobserved households’ characteristics which may be a source of bias following Mundlak’s (1978) approach. The econometric findings show that the effect of crop diversification on poverty levels varies depending on the degree of a farm household’s access to roads. The higher the distance to road, the lower the reduction of poverty due to crops diversification. Therefore, by removing access to road constraints, the Nigerienne government could leverage the benefits of crop diversification strategies on poverty reduction.